The politics of truth at LGBTQ+ Pride: contesting corporate Pride and revealing marginalized lives at Hong Kong Migrants Pride - Conway, Daniel (International feminist journal of politics, 2023)
This article focuses on the articulation of lesbian, gay, bisexual, trans, and queer (LGBTQ+) identities, lives, and rights at Pride events in Hong Kong. I argue that analyzing Pride as a Foucauldian "regime of truth" reveals how it is embedded in and reproduces broader ideological effects and structures of global capitalism. Focusing specifically on the corporate Out Leadership Asia Summit and Hong Kong Migrants Pride, organized by migrant domestic worker (MDW) unions and LGBTQ+ activists, the article explores transnational discourses of "global homocapitalism" that frame LGBTQ+ identities in individual and economically productive terms. By contrast, Migrants Pride highlights the exploitation of work and the precarity of MDWs and forges intersectional alliances with the feminist social justice movement. These differing conceptions of LGBTQ+ lives and needs form a contested "politics of truth" that exposes the tense and incongruous relationships between local and global, neo-liberal and collective, and rich and poor that underpin the dynamics of privilege and marginality of LGBTQ+ subjects in Hong Kong. The article argues that Pride's co-option is an uneven and shifting process across global contexts. Migrants Pride, by enacting queer resistance to discourses of "corporate Pride," offers a case study of how Pride can be a platform for social justice activism.